2017
DOI: 10.22159/ajpcr.2017.v10i9.18369
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance in Carbapenem-Resistant Klebsiella Pneumoniae Strains

Abstract: Objective: There is an increasing use of colistin consequent to increase in the infections caused by carbapenem-resistant Klebsiella pneumoniae. The present study was conducted to determine the minimum inhibitory concentration (MIC) of colistin and the resistance pattern of colistin in carbapenem-resistant K. pneumoniae (CRKP) strains in our intensive care unit (ICU).Methods: Antibiotic susceptibility testing for other antimicrobial agents was done by Kirby-Bauer disk diffusion method. MIC of colistin was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
5
1
0
Order By: Relevance
“…In the present study, Klebsiella pneumoniae was most frequently isolated from respiratory specimen i.e., endotracheal tube secretion (n=6) and bronchial wash (n=2) which was followed by pus specimen (n=3), blood (n=2), urine (n=2) and sputum (n=2). Similar findings were reported [24] in their research. However Goel [10] reported all colistin resistant klebsiella pneumonia in blood samples followed by respiratory specimens, aspirates and pus.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, Klebsiella pneumoniae was most frequently isolated from respiratory specimen i.e., endotracheal tube secretion (n=6) and bronchial wash (n=2) which was followed by pus specimen (n=3), blood (n=2), urine (n=2) and sputum (n=2). Similar findings were reported [24] in their research. However Goel [10] reported all colistin resistant klebsiella pneumonia in blood samples followed by respiratory specimens, aspirates and pus.…”
Section: Discussionsupporting
confidence: 92%
“…The various samples with colistin resistance organisms in the present study was seen maximum in endotracheal tube secretion (34.3%), urine (18.7%) followed by bronchial wash (12.5%), pus (12.5%), blood (9.3%) and sputum (6.25%) which was comparable to the study by Bhasker et al [24] where they also found colistin resistance organisms maximum in tracheal secretion (33.73%) followed by blood (24.3%), urine (17.9%), pus (6.7%), bronchoalveolar lavage (6.4%), catheter tips (4.5%), fluid (3.95%) and tissue (2.4%). In the study by Arjun et al [9] also found urine sample (33%) as a major source of colistin resistant isolate followed by respiratory samples (20.8%), pus (16.67%), blood (6%) and also in cerebrospinal fluid (4.17%) whereas Pawar et al [8] reported colistin resistant bacilli from pus (42.3%), followed by catheter tip (19.7%), urine (16.7%), and endotracheal tube secretion (9.1%), sputum (9.1%) each.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations